Trauma and Remembering: From Neuronal Circuits to Molecules - Szabolcs Kéri (Life, 2022)
Individuals with posttraumatic stress disorder (PTSD) experience intrusions of vivid traumatic memories, heightened arousal, and display avoidance behavior. Disorders in identity, emotion regulation, and interpersonal relationships are also common. The cornerstone of PTSD is altered learning, memory, and remembering, regulated by a complex neuronal and molecular network. We propose that the essential feature of successful treatment is the modification of engrams in their unstable state during retrieval. During psychedelic psychotherapy, engrams may show a pronounced instability, which enhances modification. In this narrative review, we outline the clinical characteristics of PTSD, its multifaceted neuroanatomy, and the molecular pathways that regulate memory destabilization and reconsolidation. We propose that psychedelics, acting by serotonin-glutamate interactions, destabilize trauma-related engrams and open the door to change them during psychotherapy.